FLOWERS AND LIVING PLANTS TRANSPORT - Poliakova, Adela (Doprava a spoje, 2009)
Quality of imported flowers and living plants is markedly influenced by condition during storage and transport. There are many existing theories and studies aimed on flowers and plants transport abroad. There is no unified regulation that would regulate the transport of this commodity in compliance with recognized principles of the nature or living environment protection in Slovak Republic. The area of the flowers transport is related only to the Ordinance of Ministry of Agriculture of Slovak Republic from 27th January 1999 Nr. 2785/1998-100 about phytosanitarian conditions in import, export and transfer of plants, plant products, also the things what would be the harmful organism carriers. Quality and vaselife may be increased by cooling flowers prior to packing. And it is also necessary to follow the temperature during storage and transport.